2018
DOI: 10.1016/j.otsr.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Medial meniscus posterior root tear induces pathological posterior extrusion of the meniscus in the knee-flexed position: An open magnetic resonance imaging analysis

Abstract: IV: retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 26 publications
2
38
1
1
Order By: Relevance
“…Duration from painful popping event to surgery was 84.4 ± 68.2 days. The presence of the MMPRT was defined according to characteristic MRI findings such as cleft, giraffe neck, ghost, radial tear, and meniscal extrusion signs of the MM posterior root within 9 mm from the attachment [19][20][21]. We divided the patients into two groups to compare the tibial tunnel position between the UMR guide (Arthrex) and the MMPRT guide (Smith & Nephew).…”
Section: Methodsmentioning
confidence: 99%
“…Duration from painful popping event to surgery was 84.4 ± 68.2 days. The presence of the MMPRT was defined according to characteristic MRI findings such as cleft, giraffe neck, ghost, radial tear, and meniscal extrusion signs of the MM posterior root within 9 mm from the attachment [19][20][21]. We divided the patients into two groups to compare the tibial tunnel position between the UMR guide (Arthrex) and the MMPRT guide (Smith & Nephew).…”
Section: Methodsmentioning
confidence: 99%
“…An open MRI analysis found that MMPRT caused pathological posterior extrusion of the MM medial and posterior segment at 90° knee flexion [23,24]. Therefore, analysis of MM medial/posterior extrusion (MMME/MMPE) in older patients after transtibial fixation of MMPRT using open MRI is clinically useful in assessing MM conditions, especially at 90° knee flexion.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this effect of tibiofemoral subluxation on the mechanics of the medial knee compartment, tibiofemoral subluxation may increase the incidence of intercondylar notch and tibial eminence impingement. Considering that the medial meniscus (MM) plays a role as a secondary stabilizer during tibial translation [8], with a posterior root tear, the MM is displaced medially and posteriorly [2,9]. This displacement may induce pathological movements at the knee joint, including a tibiofemoral subluxation.…”
Section: Introductionmentioning
confidence: 99%